2011
DOI: 10.1002/stc.422
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive pendulum for evolving structures

Abstract: Tuned mass dampers (TMDs) supplement existing structures with damping while preserving stability. As evolutions of the structure to be controlled may pull down the performance of this kind of device, large bridges under construction in windy areas are rather equipped with active devices such as AMDs that prove efficient (7th International Seminar on Seismic Isolation, Passive Energy Dissipation and Active Control of Vibrations of Structures, Assisi, Italy, 2001). However, active devices suffer from several dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…To obtain the same objective (i.e. supress wind-induced vibrations during construction), an alternative semi-active technique was also presented 68 ; the TMD control approach was based on an electromechanical device consisting of a pendulum coupled to an alternator that was used to convert the mechanical energy of the oscillating pendulum into electric energy, which in turn was dissipated through an exterior resistor via Joule effect. With regard to earthquake induced excitation, a passive, a semi-active and an active tuned mass damping system were investigated 69 for the case of motorway bridges.…”
Section: Controllable Tuned Mass Dampers and Tuned Liquid Dampersmentioning
confidence: 99%
“…To obtain the same objective (i.e. supress wind-induced vibrations during construction), an alternative semi-active technique was also presented 68 ; the TMD control approach was based on an electromechanical device consisting of a pendulum coupled to an alternator that was used to convert the mechanical energy of the oscillating pendulum into electric energy, which in turn was dissipated through an exterior resistor via Joule effect. With regard to earthquake induced excitation, a passive, a semi-active and an active tuned mass damping system were investigated 69 for the case of motorway bridges.…”
Section: Controllable Tuned Mass Dampers and Tuned Liquid Dampersmentioning
confidence: 99%
“…The optimal parameters of the pendulum TMD are obtained from a new design [17]. The semi-active control is achieved by just changing the resistor in real time according to a control law [18]. The proposed goal is to keep the same electromechanical actuator during the main construction steps and to change its apparent stiffness and damping through a semi-active control law.…”
Section: Introductionmentioning
confidence: 99%
“…Since Frahm et al proposed the fundamental theory, TMDs have seen numerous applications in civil engineering [11][12][13]. Thus, Ben Mekki and Bourquin [14,15] proposed a new semi-active electromagnetic TMD of pendulum type to damp the torsional mode of an evolving bridge mock-up. Their studies showed that the tuned pendulum damper (TPD) is very effective in vibration damping, In this way, the role of the springs and dampers can be replaced by a control force vector, where the control gain is composed of the spring stiffness and damping coefficients (ki and ci for i = 1, 2, …, 6).…”
Section: Introductionmentioning
confidence: 99%